Staff motivation and schools' capacities to sustain an intervention to prevent bullying and promote wellbeing in English secondary schools: a qualitative study - Herlitz, Lauren; Bonell, Chris (Frontiers in Public Health, 2025)
IntroductionDiscontinuing effective school health interventions prevents new practices from reaching wider student populations and wastes investment in implementation. While reviews have consistently identified facilitators and barriers to the sustainment of school health interventions, the social processes underlying sustainment remain unclear. We explored the post-trial sustainment of “Learning Together,” a whole-school intervention, found to be effective in preventing bullying and promoting wellbeing in English secondary schools. We examined how staff and students described its sustainment in the 2 years post-trial, what factors staff referred to in explaining their motivation to sustain it, and how schools' capacities affected sustainment.Methods and materialsLearning Together involved training staff in restorative practice (RP) and supporting schools to implement a staff-student action group and a social and emotional learning curriculum. Using a case-study design, we collected qualitative data from five schools: staff and student interviews 1-year post-trial; staff interviews 2 years post-trial; and descriptive data from the original trial's process evaluation. The General Theory of Implementation guided our thematic analysis.ResultsNo school sustained the intervention in its entirety. RP was continued by some individuals in all schools and was sustained at school-level in one school. The curriculum and action groups were discontinued in all schools, although actions initiated by the groups were sustained in two schools. Staff motivation to sustain components was affected by their perceived effectiveness, and individual motivations to sustain RP differed from whole-school commitment to sustaining the approach. Schools' capacities to sustain Learning Together were affected by: the prioritization of academic learning time; the frequent implementation of new initiatives; the timeliness of interventions with school improvements plans; and leadership engagement. Schools needed support to disseminate RP knowledge and skills school-wide and ensure consistent practice, and turnover adversely impacted on knowledge transfer.DiscussionSustainment was an intentional, labor-intensive, social process. Intervention developers should consider whether/how interventions are designed to work alongside, replace, or can refine existing practices, and should support schools to mainstream evidence-based interventions to sustain them at school-level.